CT Abdominal Tomography Indications: Are We All Sticking to the Plan?. Issue 4 (November 2021) - Pyper, Michael; Sidiqi, Abdulwahab; Rogalla, Patrik; Sabbah, Sam; Kielar, Ania
Objective: Ultra-low radiation dose computed tomography (CT) abdominal tomography was introduced in our institution in 2016 to replace standard abdominal radiography in the investigation of emergency department patients. This project aims to ascertain whether investigation of emergency department patients using ultra-low radiation dose CT abdominal tomography complies with original indication guidelines and/or if there has been any "indication creep" 3 years after inception. Methods: Retrospective, quality assurance project with research ethics waiver. A review of 200 consecutive patients investigated with CT abdominal tomography between February and May 2017 was performed. This was compared with 200 consecutive patients investigated between February and May 2019. Data analyzed included patient demographics, indication for scan, as well as scan and patient outcomes. Results: In the 2017 group, 29/200 scans were noncompliant with approved indication guidelines. In the 2019 group, 30/200 scans were also noncompliant. There was no statistically significant difference between groups ( P < .05) regarding the use of approved indications. Forty of 200 scans performed in 2017 revealed additional findings which are not specifically addressed on the reporting template. Forty-one of 200 scans in 2019 revealed these findings. Conclusions: There has been no "indication creep" for CT abdominal tomography over time.